MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAK DENGAN MENGGUNAKAN METODE LEARNING START WITH A QUESTION DI KELAS V SD NEGERI 173172 HUTAGURGUR KAB. TAPANULI UTARA - Martini Srianita Hutabarat (Pusat Riset dan Inovasi Nasional, 2023)
Abstract, This research was conducted at SD Negeri 173172 Hutagurgur Kab. North Tapanuli, this type of research is classroom action research using the Learning Start With a Question learning method as the main target aiming to improve student learning outcomes using the Learning Start With a Question learning method to improve student learning outcomes in social studies lessons in Class V SD Negeri 173172 Hutagurgur Kab. North Tapanuli. To obtain the data used in this study the authors conducted tests and observations. The data analysis technique in this study is a qualitative description by describing the percentages used. After carrying out the pre-test, it was obtained that the level of mastery of learning outcomes was classical, namely 2 students (8.3%) who achieved a level of mastery learning with an average value of 29.9. After the implementation of the first cycle using the Learning Start With a Question learning method, it was obtained that the level of completeness of learning outcomes in a classical manner was 11 students (45.83%) who achieved a level of learning completeness with an average score of 55.93. After the implementation of the second cycle using the Learning Start With a Question learning method, it was obtained that the level of completeness of learning outcomes in a classical manner was 21 students (87.5%) who achieved a level of learning completeness with an average score of 80.3. Thus, it can be said that learning activities using the Learning Start With a Question learning method can improve student learning outcomes in Class V SD Negeri 173172 Hutagurgur Kab. North Tapanuli in PAK lessons